Emerging Role of Olanzapine for Prevention and Treatment of Chemotherapy‐Induced Nausea and Vomiting. Issue 2 (February 2016) - DeRemer, David L.; Clemmons, Amber B.; Orr, Julianne; Clark, Stephen Michael; Gandhi, Arpita Shah
Abstract : The prevention and treatment of chemotherapy‐induced nausea and vomiting (CINV) continues to pose a challenge for clinicians. The development of 5‐hydroxytryptamine (serotonin) antagonists and neurokinin‐1 receptor antagonists (NK1 ‐RAs) have demonstrated significant improvements in acute and delayed CINV for highly and moderately emetogenic chemotherapy. Delayed and breakthrough CINV, however, continue to be difficult to manage despite available treatment agents. Randomized clinical trial data suggest that olanzapine, a second‐generation thienobenzodiazepine, traditionally used in the treatment of manifestations of psychotic disorders, is an effective agent in these clinical settings. The short‐term use of olanzapine has a favorable adverse event profile and was not associated with grade 3 or 4 toxicity in a phase III study. Olanzapine is recommended as an option within first‐line prophylaxis for CINV in the National Comprehensive Cancer Network (NCCN) guidelines and is an option for treatment of refractory CINV in the Multinational Association of Supportive Care in Cancer/European Society for Medical Oncology and NCCN guidelines.